ANALISIS PENGGUNAAN APLIKASI KASIR TERHADAP EFEKTIVITAS PELAYANAN KONSUMEN PADA UMKM LAPATHU PS DI KECEMATAN PANCA RIJANG - Marlia, Indar Novia; Rahmat Razak, Muhammad Rais; Sofyan, Wahyudi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
In this period of improvements in science and innovation as well as high rivalry in an undeniably progressed business world, it makes it simpler for us to work rapidly and productively. Numerous MSMEs in the Panca Rijang sub-region have used cutting edge innovation in their business fields. One of them is executing a clerk application to oversee deals exchanges and make it more straightforward to gather monetary report information. An issue that is much of the time tracked down in endeavors to further develop client support is that shopping strikes are frequently not printed. The reason for this exploration is to figure out how the clerk application utilized by Lapathu PS UMKM further develops client care. The strategy utilized is subjective with the exploration objects being proprietors, workers and shoppers who do buy exchanges without receipts. Information assortment strategies are perception, meetings and documentation. This examination was directed at UMKM Lapathu PS, definitively on Jalan AP Pettarani No, 20. The exploration results show that in the wake of utilizing the clerk application at Lapathu PS MSMEs, the business cycle can be made more powerful and accelerate administration to customers. Keywords: